Poly(o-ethylaniline) coatings for stainless steel protection - Chaudhari, Sudeshna; Sainkar, S. R.; Patil, P. P. (Progress In Organic Coatings, 2007)
The poly(o-ethylaniline) coatings were electrochemically synthesized on 304-stainless steel by using cyclic voltammetry from an aqueous salicylate medium. Cyclic voltammetry, UV-vis absorption spectroscopy, Fourier transform infrared spectroscopy and scanning electron microscopy were used to characterize these coatings, which indicates that the aqueous salicylate solution is a suitable medium for the electrochemical polymerization of o-ethyaniline on 304-stainless steel. The performance of poly(o-ethylaniline) as protective coating against corrosion of 304-stainless steel in aqueous 3% NaCl was evaluated by the open circuit potential measurements, potentiodynamic polarization technique, cyclic potentiodynamic polarization measurements and electrochemical impedance spectroscopy. The results of the potentiodynamic polarization and cyclic potentiodynamic polarization demonstrate that the poly(o-ethylaniline) coating provides excellent protection to both localized and general corrosion of 304-stainless steel. The corrosion potential was about 0.190 V more positive in aqueous 3% NaCl for the poly(o-ethylaniline) coated steel than that of bare steel and reduces the corrosion rate of steel almost by a factor of 20. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Conducting polymer coatings; Corrosion resistant coatings; cyclic voltammetry; Electrochemical polymerization; poly(o-ethylaniline) coatings; stainless steel